Combination of Core Activation and Curl-Up Exercise on Reducing Diastasis Rectus Abdominis (DRA) in Multiparous Women - Woli, Yuniatri; Listyawati, Luh Putu Ayu Vita; Putri, Ni Made Rininta Adi; Larashati, Ni Putu Dwi (Poltekkes Kemenkes Surakarta, 2025)
Background: Pregnancy and childbirth cause physical changes in women, including pelvic floor muscle weakness and abdominal wall enlargement leading to the condition of Diastasis Recti Abdominis (DRA). Multiparous women are at higher risk of experiencing DRA due to repeated stretching of the abdominal wall. This study aimed to evaluate the effectiveness of combining core activation with curl-up exercises in reducing the degree of DRA in multiparous women. Methods: This study was conducted in Desa Homba Rande using a pretest-post test control group design. A total of 24 multiparous women were selected through purposive sampling and divided into two groups: intervention (n=12) and control (n=12). The intervention group received core activation and curl-up exercises three times a week for 12 weeks. Inter-recti distance was measured using a digital caliper before and after the intervention period. Data were analyzed using the Paired T-Test and Independent T-Test. Results: All research samples were multiparous women aged 20-45 years, with controlled BMI, type of delivery, number of pregnancies, number of births, and physical activity score (IPAQ-SF). The paired t-test showed a p-value of 0.001 (p<0.05), indicating a significant improvement after intervention. The independent t-test showed a p-value of 0.002 (p<0.05), indicating a significant difference in post-test data between groups. Conclusion: Core activation combined with curl-up exercises is effective in reducing DRA in multiparous women. These exercises are recommended as part of routine postpartum rehabilitation to improve core strength and function.